Pengaruh Bahan Ajar Metodologi Sejarah Terhadap Kecepatan Penulisan Skripsi Mahasiswa di Program Studi Pendidikan Sejarah FKIP Universitas Sriwijaya - Alian Sair; Dedi Irwanto (Criksetra: Jurnal Pendidikan Sejarah, 2015)
The aim of this study was to determine the effect of Instructional Materials Methodology and Historiography History to speed the writing of a student in the Department of History Education Studies Program IPS FKIP Sriwijaya University. This study is a research development. The instrument used was a questionnaire, a questionnaire and documentation. Data were analyzed by using descriptive analysis of qualitative and quantitative descriptive statistical analysis. Based on the research results of field trials to test 66 students in the development of teaching materials Methodology and Historiography History decent used for learning at home, in addition to the class, so demanding independence and the acceleration of research and writing of history mahasisiwa. Based on comparative data obtained that if the academic year 2012/2013 the average completion of the writing of history students have a time range between 24-48 Sunday means for 6 months to one year. While in the academic year 2013/2014 the average settlement of the writing of history students aided by modeling methodology of teaching materials History and Historiography only between 12-24 months (approximately 3 months)